Analysis of User Satisfaction with the Mnet Plus Application Using the End-User Computing Satisfaction Method - Gunawan Witjaksono; Nanda Silva (INOVTEK Polbeng - Seri Informatika, 2025)
The development of the global entertainment industry, especially K-pop, has driven innovation in digital applications. Mnet Plus, a mobile-based application, is designed to enhance user experience with various interactive features. Mnet Plus created a communication platform that provides an experience for global users to enjoy K-pop content. However, in its use, there are still several problems that make users less satisfied with the application. This issue is important to address because user satisfaction is the main indicator of an application's success and can influence loyalty and continued use. This research aims to determine the level of user satisfaction and the factors influencing it on the Mnet Plus application. This research uses a quantitative approach and the End User Computing Satisfaction (EUCS) method with five variables, namely content, accuracy, format, ease of use, and timeliness. Data collection was carried out by distributing questionnaires to users of the Mnet Plus application and then processing it using the SPSS 25 program for further analysis. The results of the analysis that was carried out show that of the five hypotheses that were partially tested, two hypotheses were rejected, namely the content and format variables. Simultaneously, the five variables have a significant effect on user satisfaction of the Mnet Plus application. The practical implication of these findings is the need for application developers to prioritize technical performance improvements, interface simplification, and feature timeliness.